Struggling to breathe: COVID-19, protest and the LIS response. Issue 1 (3rd August 2020) - Gibson, Amelia N.; Chancellor, Renate L.; Cooke, Nicole A.; Dahlen, Sarah Park; Patin, Beth; Shorish, Yasmeen L.
Abstract : Purpose: The purpose of this article is to provide a follow up to "Libraries on the Frontlines: Neutrality and Social Justice, " which was published here in 2017. It addresses institutional responses to protests and uprising in the spring and summer of 2020 after the deaths of Ahmaud Arbery, Breonna Taylor and George Floyd, all of which occurred in the context of the global COVID-19 pandemic. The article expands the previous call for libraries to take a stand for Black lives. Design/methodology/approach: The authors describe the events of 2020 (a global pandemic, multiple murders of unarmed Black people and the consequent global protests) and responses from within library and information science (LIS), from the perspectives as women of color faculty and library professionals. Findings: The authors comment on how libraries are responding to current events, as well as the possibilities for panethnic solidarity. The authors also consider specifically how libraries and other institutions are responding to the racial uprisings through statements on social media and call for concrete action to ensure that their organizations and information practices are actively antiracist. In so doing, the authors update the claims and expand the appeals they made in 2017, that Black Lives Matter and that librarianship must not remain neutral. Originality/value: This paper addresses recent institutional and governmental reactions to the COVID-19 pandemic and the racial uprisings of spring and summer 2020. It is original, current and timely as it interrogates ongoing events in a LIS context.